Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top


Describe the locus of the following points on the Argand diagram:

$$\left|\frac{(z+1-i)}{(z-1-i)}\right| = 1$$ and

$$\mathrm{arg}\left[\frac{(z+1+i)}{(z-1-i)}\right] = \pm \frac{\pi}{2}.$$


I've tried putting $z = x+iy $ then rationalising the denominator by multiplying by the conjugate which gave me some numbers, but I'm not sure what to do with them.

I would really love some help on these 2 questions, all responses much appreciated!

share|cite|improve this question
What have you tried? Are you confused with some particular step? It helps for us to know. Regards – Amzoti Apr 1 '13 at 4:12
I've tried putting z = x+iy then rationalising the denominator by multiplying by the conjugate which gave me some numbers, but I'm not sure what to do with them. – Andy Apr 1 '13 at 4:22

to answer the second one $$arg\left({z + 1 + i \over z - 1 -i} \right) = \pm {\pi \over 2}$$ is a circle with diameter $1+i, -1-i.$

here is how you can see this: let $${z + 1 + i \over z - 1 -i} = ki \text{ where $k$ is a real number}$$ you can dove for $z$ and get $$z = {-ki +k - 1 -i\over 1 -ki} = {[k-1 -i(k+1)] \over 1 - ik} = {[k-1 -i(k+1)](1 + ik) \over 1 + k^2} \\= {k-1 + k(k+1) + i[k(k-1)-(k+1)] \over 1 + k^2} = {k^2+ 2k - 1 + i(k^2 - 2k - 1) \over 1 + k^2}$$

if $z = x = iy,$ then $$x = {k^2 - 1 + 2k \over k^2 + 1}, y = {k^2 - 1 - 2k \over k^2 + 1} $$ which gives $$x^2 + y^2 = { 2(k^2 - 1)^2 + 8k^2 \over (k^2 + 1)^2} = { 2(k^2 + 1)^2 \over (k^2 + 1)^2} = 2$$ as claimed at the beginning.

if you look at the geometry of the problem, it says the angle subtended by the point $z$ by the points $\pm(1+i)$ is $90^\circ$ which is the locus of a circle. to derive it algebraically i had to go through all the trouble.

share|cite|improve this answer

The first one is saying that the distance between $z$ and $1 + i$ is the same as the distance between $z$ and $1 - i$. The set of points equidistant from two points is the line bisecting the line segment joining the two points. Hence, the locus is the line $y = 0$.

The second one is saying if you look at the point $P$ given by translating $z$ 1 up and 1 to the right and the point $Q$ given by $z$ translated 1 down and 1 to the left, the angle between $P$ and $Q$ (with respect to the origin) is $\pi/2$. Intuitively, this seems to me to be the line $y = x$, though I haven't checked this rigorously.

share|cite|improve this answer
Ok thank you for the explanations, so for the first question it's simply the line x=0? Also, for the second question, I thought the angle was always taken between the positive direction of the horizontal - so from which point would we take the angle (does it matter)? – Andy Apr 1 '13 at 4:25
Ooops, I meant $y = 0$, but yes, that's the answer. As for the second one, arg of a quotient is the angle between the numerator and the denominator. (Because multiplying two complex numbers results in the angles that they make with the positive horizontal axis being added) – Jonah Sinick Apr 1 '13 at 4:35

$$\left|\frac{(z+1-i)}{(z-1-i)}\right| = 1$$ $$\left|\ (z+1-i)\right| = |(z-1-i)|$$ put z=x+iy $$\left|\ (x+iy+1-i)\right| = |(x+iy-1-i)|$$ $$\left|\ (x+1)+i(y-1)\right| = |(x-1)+i(y-1)|$$ $$\left|\ (x+1)+i(y-1)\right|^2 = |(x-1)+i(y-1)|^2$$ since $$\left|\ (x+iy)\right|^2 = x^2+y^2$$ then $$\left|\ (x+1)+i(y-1)\right|^2 = |(x-1)+i(y-1)|^2$$ $$ (x+1)^2+(y-1)^2=(x-1)^2+(y-1)^2 $$ $$(x+1)^2=(x-1)^2$$ $$x=0$$ equation of Y-axis.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.